The interaction of dengue cases between climatic factors and air pollutants in Peninsular Malaysia / Mohamad Khushairi Muhd Nor - Muhd Nor, Mohamad Khushairi (2023)
Aedes aegypti and Aedes albopictus had caused dengue in tropical and subtropical regions. Vector control is used for minimizing dengue cases, unfortunately, it relies on climatic and environmental variables which introduce the complex relationship in analysing dengue cases. Thus, this study aims in assessing the interaction of dengue cases between climatic factors and air pollutants in Peninsular Malaysia by using Principal Component Analysis (PCA). Secondary data on dengue cases, climatic factors from the year 2016 until 2020 are obtained from Ministry of Health (MOH) and Department of Environment (DOE), Malaysia, respectively. Results show among 91 districts in Peninsular Malaysia, 47.1% are denoted as hot spot (high prevalence of dengue cases) and 53.9% are classified as cold spot (low number of dengue cases).